The Effectiveness Comparison of Valproic Acid 500 mg and Amitriptyline 15 mg in Reducing the Frequency of Headache Attack in Patients with Tension-Type Headache - Elsa Susanti1, Isti Suharjanti1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Tension-type headache (TTH) is the most common headache. Continuous analgesic use can develop into headache caused by drug abuse (medication overused headache); thus, the preventive therapy is necessary. Amitriptyline and valproic acid are drugs reported to reduce the frequency of headache in TTH patients. Objective: To analyze the effectiveness of valproic acid 500 mg and amitriptyline 15 mg in reducing the frequency of headache attack in patients with tension-type headache. Methods: The study applied a Double Blind Randomized Clinical Trial involving 50 TTH patients. The subjects were divided into two groups: amitriptyline 15 mg and valproate acid 500 mg. The period of drug administration was 6 weeks. The variables that were compared were the decreasing frequency of headache and the intensity of the pain. Results: There was no significant difference in the decrease of headache frequency (p = 0.730) and pain intensity (p = 0.430) between the amitriptyline group and valproate acid group. However, each drug effectively decreased the frequency of headache and pain intensity in TTH patients (p = 0.000). Conclusion: There was no significant difference between the effectiveness of valproic acid 500 mg and amitriptyline 15 mg in reducing the frequency of headache in patients with TTH.